The Analysis of Economics Students’ Lack of Grasp toward English Business Subject at Second Semester of Widyaswara Indonesia Campus - Putri, Riza Eka (Jurnal Penelitian Multidisiplin Bangsa, 2024)
This study aimed to analyze the students’ lack of grasp in learning the glossaries of economics and business terms and their obstacles in practicing the useful expressions often used in various conversation material relate with the economics and business activities often occur in the area of business or industrial or companies communities. This was kind of descriptive qualitative research. The samples were 27 students at second semester of Economics Students. The technique used for collecting the data were observation and interview. The observation was conducted for 16 meeting included midterm test and final test. The interview was conducted at the end of semester. Furthermore, the data were analyzed by describing their activities in the classroom, particularly paying attention students’ abilities and creativities in discussion session, assessing their comprehension through the tasks, exercise, quiz, homework, presentation and examination. Finally, the analysis process was strengthened by connecting the data found with the interview result. Indeed, the study of these phenomenon could be answered, the researcher could find out the factors influence students’ lack of grasp in comprehending the English Business subject. The result showed that the reason of students’ lack of grasp and their weaknesses were mostly come from themselves where almost all of them in the classroom had less motivation to learn English and they didn’t also understand the purpose of learning English Business Subject. In short, they did not realize the importance of English in real life activities especially working horizon.